The Quest for Good Urban Governance Theoretical Reflections and International Practices - van den Dool, Leon.; Hendriks, Frank; Gianoli, Alberto; Schaap, Linze; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2015)
This book demonstrates both successes and failures in attempts to get closer to the ideal of good urban governance in cities in North-America, Europe, and Asia. It presents a value menu and deliberately does not come up with (3z(Bone best way(3y (Bfor improving urban governance. Good urban governance is presented as a balancing act, an interplay between government, business and civil society in which the core values need careful and timely attention. The authors address questions such as (3z(BWhat is deemed (3z(Bgood(3y (Bin urban governance, and how is it being searched for?(3y(B, and (3z(BWhat (re)configurations of interactions between government, private sector and civil society are evolving, and to what results?(3y(B. Contents Reflections on Good Governance Designing Good Urban Governance Partnerships in European, Indian and Chinese Cities Multi-level Governance Citizen Participation Target Groups Lecturers and Students of Sociology, Urban Studies, Public Administration, Political Science, Development Studies Practitioners in Cities all over the World The Authors Leon van den Dool is Senior Researcher at Tilburg University and Senior Manager at PwC Advisory in the field of Local Government, the Netherlands. Frank Hendriks is Professor in Comparative Governance at Tilburg University, the Netherlands. Alberto Gianoli is Senior Expert in Urban Governance at the Institute for Housing and Urban Development Studies (IHS) in Rotterdam, the Netherlands. Linze Schaap is Associate Professor Public Administration at Tilburg University, the Netherlands.s
Reflections on Good Governance -- Designing Good Urban Governance -- Partnerships in European, Indian and Chinese Cities -- Multi-level Governance -- Citizen Partizipation.
Keywords: Political science; Political theory; Comparative politics; Political Science and International Relations; Comparative Politics; Political Theory; Electronic books